Associations Between Physical Activity and Alcohol Consumption in Rural Cancer Survivors - Mama, Scherezade K.; Heredia, Natalia I.; Johnston, Hannah; Conroy, David E. (Frontiers in Oncology, 2022)
Purpose: Rural adults and cancer survivors are more likely to be physically inactive and exceed recommendations for alcohol use. Physical activity and alcohol use are positively associated in adults and cancer survivors, but associations between physical activity and alcohol use in rural cancer survivors is unknown. This cross-sectional study explored associations between physical activity, sitting time and alcohol use in rural cancer survivors. Methods: Cancer survivors residing in central Pennsylvania were recruited to the Partnering to Prevent and Control Cancer (PPCC) study and completed mailed questionnaires assessing physical activity (low, moderate, high), sitting time (<6 or ≥6 hours/day), and alcohol use (0 or ≥1 drinks/week). Binary logistic regression models tested associations between physical activity, sitting time and alcohol use, adjusting for age, gender, and education. Results: Participants (N=219) were in their mid-60s (M age=64.5±12.2 years, 60.7% female), overweight (M BMI=29.6±6.9 kg/m2), and 50.5% were college graduates. Nearly half of participants were breast (22.8%) or prostate (20.5%) cancer survivors, and 90.4% were >12 weeks but <5 years post-treatment. Participants self-reported meeting physical activity recommendations (79.5%), sitting <6 hours/day (53.3%), and consuming ≥1 alcoholic drinks/week (54.1%). Participants who reported being moderately (OR=5.0, 95% CI: 1.9-12.9) or highly (OR=4.5, 95% CI: 1.9-10.9) active had higher odds of reporting alcohol use, after adjusting for covariates. Conclusion: Results mirror positive associations seen in adults and other subgroups (e.g., racial/ethnic minority adults). Cancer control efforts should stress being physically active while emphasizing messaging to curtail increases in alcohol use among rural cancer survivors.